2005
DOI: 10.1177/1471301205055029
|View full text |Cite
|
Sign up to set email alerts
|

Equipping staff to support people with an intellectual disability and dementia in care home settings

Abstract: The knowledge, experiences and skills of direct care staff working in care home settings are essential in ensuring a good quality of life and care for a person with an intellectual disability (ID) who develops dementia. Drawing on the findings of a wider study, the issues of training, support and the wider needs of staff when trying to support a resident who develops dementia are explored, specifically as relating to the role played by staff and the need to determine their experiences and related training need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
130
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(136 citation statements)
references
References 12 publications
(22 reference statements)
5
130
0
Order By: Relevance
“…As found by Bates et al (2004) and Wilkinson and Kerr (2005), many support workers in this study received no specific mental health training and were uncertain how to apply their knowledge. Most made incorrect judgements about the meanings of some mental health symptoms, echoing Costello et al's (2007) findings.…”
Section: Discussionmentioning
confidence: 80%
“…As found by Bates et al (2004) and Wilkinson and Kerr (2005), many support workers in this study received no specific mental health training and were uncertain how to apply their knowledge. Most made incorrect judgements about the meanings of some mental health symptoms, echoing Costello et al's (2007) findings.…”
Section: Discussionmentioning
confidence: 80%
“…The demand for a method to handle problems associated with the ageing of people with intellectual disability (as dementia) we found is widely reflected in studies of experiences of staff in working with adults and older people with intellectual disability (Cleary & Doodey, 2016;Furniss, Loverseed, Lippold, & Dodd, 2012;Iacono et al, 2014;McCarron, McCallion, Fahey-McCarthy, Connaire, & Dunn-Lane, 2010;Perera & Standen, 2014;Watchman, 2014;Wilkinson et al, 2005). Several studies of DCM in nursing home settings reported difficulties similar to ours in fulfilling the DCM-preconditions.…”
Section: Discussionmentioning
confidence: 92%
“…quality of care SCHAAP et Al. dementia (Cleary & Doodey, 2016;Duggan et al, 1996;Emerson, 2001;Iacono, Bigby, Carling-Jenkins, & Torr, 2014;Myrbakk & von Tetzchner, 2008); they tend to use an ad hoc approach (Iacono et al, 2014;Janicki, 2011;Janicki, McCallion, & Dalton, 2002;Watchman, 2008;Wilkinson, Kerr, & Cunningham, 2005). Therefore, an evidence-based method that provides insights, knowledge and skills for professionals in the care of older residents with intellectual disability and dementia is urgently needed, but not yet available.…”
mentioning
confidence: 99%
“…Support for staff in dementia care is crucial to provide an effective approach to planning resourcing and support (Wilkinson, Kerr, & Cunningham, 2005). Moreover, Singh (2005) stressed that social and residential orientation of institutional settings should be characterized by shared control in management, and that care goes beyond the medical context.…”
Section: Downloaded By [Northeastern University] At 22:58 11 October mentioning
confidence: 99%